Responsible artificial intelligence use as educational empowerment: Governance, critical literacy, and lifelong learning - Nicolaus Petrus Likuwatan Werang; Sri Putri Ramadhani; Maria Lusiana Florentin Werang; Rizky Amalia Putri (Community Service for Sustainable Community Journal, 2026)
Background: The fluctuating use of digital tools, especially artificial intelligence (AI), in higher education institutions has intensified concerns about learner protection, epistemic integrity, and academic autonomy, which underline the positioning of governance and innovation as opposing aims. Methods: This essay adopts a qualitative, conceptual research design grounded in library-based research and critical literature review, synthesizing interdisciplinary scholarship (e.g., education, ethics, information science, and educational technology). Discussion: The discussion argues that regulated access serves as an epistemic safeguard, that critical literacy is the central mechanism of governance, and that responsibility for effective tool use is collective and institutional. These conceptual insights help lay the groundwork for governance that enables responsible autonomy rather than restriction. Conclusion: Interestingly, participatory governance structures are essential for sustaining epistemic integrity while supporting educational innovation and also offer broader implications for community development and educational outreach initiatives by fostering critical engagement with digital technologies beyond higher education settings. Novelty/Originality of this article: The essay lies in reframing access governance as a form of epistemic stewardship that links regulated access to critical literacy in higher education and extends its relevance to broader educational and community contexts.